Planejamento e gestão estratégica para o restaurante universitário da UFC em um cenário de expansão do número de alunos - Maia, Tania Maria Lacerda (2008)
The present work focuses on the analysis of the impacts of the Federal University of Ceará affiliation proposal to the Reuni, concerning attendance to the University Restaurant on a result of the increasing demand, in the perspective of strategic planning and management, based on the actions carried out from 2003 to 2008. For such end, the postulates of Strategic administration and of Learning School have been adopted, having as a reference the present and future scenario and the strategic diagnosis based on the SWOT analysis. The present research (study) adopted the bibliographical, documental and action-research methods. The research shows that the foreseen expansion in the number of meals per day, from 3000 to 6000, will have an impact on the quality of the services delivered to the users, due to the present limitations in infra-structure, equipments, qualified personnel, and, above all, the need for implementing a pattern of management aimed at results. For this new scenario the following measures have been suggested, including a Strategic Plan for 2009-2020, a Tatic Plan for 2009-2012, a performance marker matrix focused on the Balanced scorecard method, besides management pattern guidelines, oriented towards results and users in the specific context of the University restaurant. The actions and management patterns proposed in the strategic plans, when adopted , will allow the University restaurant to have operational infra-structure, staff support and management excellence to assure and contribute to the approval in the service quality from the present percentage of 60.3% aiming to reach the concepts of good and excellent.